Telecentre Knowledge Sharing System - Kadum, Mohamed Adel (2012)
Telecentre embodies the principle of providing information access therefore has the potential to influence the growth of small-scale enterprises and local entrepreneurs. Currently in Malaysia, there is no system for TC manager to share information and experience; limiting their creativity and idea in organizing relevant activity to their community. The aim of this study is to develop a Telecentre Knowledge Sharing system (TKSS) to help Malaysians communities to access and share information on products and learning materials. The system was developed using C# language under ASP.net environment. Moreover, the system was evaluated based on the usability testing using IBM Computer System Usability Questionnaire (CSUQ). The prototype was assessed through a sample which consists of thirty respondents from Malaysia, and the results have been positive.